PKC epsilon‐dependent calcium oscillations associated with metabotropic glutamate receptor 5 prevent agonist‐mediated receptor desensitization in astrocytes - Vergouts, Maxime; Doyen, Pierre J.; Peeters, Michael; Opsomer, Remi; Michiels, Thomas; Hermans, Emmanuel (Journal of neurochemistry, 2017)
A critical role has been assigned to protein kinase C (PKC)ε in the control of intracellular calcium oscillations triggered upon activation of type 5 metabotropic glutamate receptor (mGluR5) in cultured astrocytes. Nevertheless, the physiological significance of this particular signalling profile in the response of astrocytes to glutamate remains largely unknown. Considering that kinases are frequently involved in the regulation of G protein‐coupled receptors, we have examined a putative link between the nature of the calcium signals and the response regulation upon repeated exposures of astrocytes to the agonist (S)‐3,5‐dihydroxyphenylglycine. We show that upon repeated mGluR5 activations, a robust desensitization was observed in astrocytes grown in culture conditions favouring the peak‐plateau‐type response. At variance, in cell cultures where calcium oscillations were predominating, the response was fully preserved even during repeated challenges with the agonist. Pharmacological inhibition of PKCε or genetic suppression of this isoform using shRNA was found to convert an oscillatory calcium profile to a sustained calcium mobilization and this latter profile was subject to desensitization upon repetitive mGluR5 activation. Our results suggest a yet undocumented scheme in which the activity of PKCε contributes to preserve the receptor sensitivity upon repeated or sustained activations. Cover Image for this issue: doi: 10.1111/jnc.13797. The activation of Type 5 metabotropic glutamate receptor (mGluR5) in astrocytic cultures triggers cytosolic calcium signals with either an oscillatory profile or a peak‐plateau profile. A critical role has been assigned to PKCε in the control of these calcium oscillations. A sustained calcium mobilization during mGluR5 activation promotes receptor desensitization, whereas a calcium oscillatory profile prevents such adaptation. In addition, activation or inhibition of PKC epsilon influences the mGluR5‐mediated calcium signalling pattern. Changes in PKC epsilon activity could therefore regulate the astrocytic response to repeated mGluR5 activation. Cover Image for this issue: doi: 10.1111/jnc.13797.